Alice Stokes Paul (1885-1977) - Jan Marie Fritz (Clinical Sociology Review)
Alice Stokes Paul was born in the United States (USA) on January 11, 1885 at Paulsdale in Mount Laurel, New Jersey. She received a Ph.D. in sociology and devoted her life to achieving rights for women. While her academic work was completed before the term “clinical sociology” was used in the United States, her work certainly should be seen as part of the history of clinical sociology.